(untitled) (IAHS Medical Journal, 2026)
Background: Bronchiolitis is the most common lower respiratory tract infection in infants and a major cause of pediatric hospitalization. Arterial Blood Gas (ABG) analysis can provide critical insights into respiratory function and disease severity, especially in moderate to severe cases. This study aimed to evaluate the arterial blood gas patterns in pediatric patients diagnosed with moderate and severe bronchiolitis at a tertiary care center. Materials and methods: This cross-sectional study was conducted in the Department of Paediatrics, Chattagram Maa-O-Shishu Hospital Medical College, Chattogram, Bangladesh, from January 2015 to July 2015. This study, included 50 pediatric patients with bronchiolitis aged 2 months to 2 years attending the OPD or admitted to the Paediatric Department of Chattagram Maa Shishu-O-General Hospital. Results: Most children were between 7–18 months old, with a male predominance (70%). Cough and respiratory distress were universal symptoms and chest indrawing with rhonchi was present in all cases. Hypoxemia (SpO2 <95%) and tachypnea (R/R >60) were common. ABG analysis revealed that most moderate cases had normal pH and elevated PaO levels, while severe cases showed higher proportions of hypoxemia and low bicarbonate levels. Hypocapnia was observed across both groups. However, no significant differences were found between moderate and severe cases for pH (p=0.503) PaO2 (p=0.432) PaCO2 (p=0.453) or HCO3 (p=0.231). Conclusion: This study showed that while ABG patterns revealed mild differences between moderate and severe pediatric bronchiolitis cases, these variations were not statistically significant. ABG analysis may still serve as a supportive tool in assessing respiratory compromise in severe cases, aiding in the early recognition of respiratory failure. IAHS Medical Journal Vol 8(1), June 2025; 71-76